Synergistic Effects on the Elderly People's Motor Control by Wearable Skin-Stretch Device Combined with Haptic Joystick - Yoon, Han U.; Anil Kumar, Namita; Hur, Pilwon (Frontiers in Neurorobotics, 2017)
Cutaneous sensory feedback can be used to provide additional sensory cues to a person performing a motor task where vision is a dominant feedback signal. A haptic joystick has been widely used to guide a user by providing force feedback. However, the benefit of providing force feedback is still debatable due to performance dependency on factors such as the user’s skill-level, task difficulty. Meanwhile, recent studies have shown the feasibility of improving a motor task performance by providing skin-stretch feedback. Therefore, a combination of two aforementioned feedback types is deemed to be promising to promote synergistic effects to consistently improve the person’s motor performance. In this study, we aimed at identifying the effect of the combined haptic and skin-stretch feedbacks on the aged person’s driving motor performance. For the experiment, fifteen healthy elderly subjects (age 72.8±6.6 years) were recruited and were instructed to drive a virtual power-wheelchair through four different courses with obstacles. Four augmented sensory feedback conditions were tested: no-feedback, force feedback, skin-stretch feedback, and a combination of both force and skin-stretch feedbacks. While the haptic force was provided to the hand by the joystick, the skin-stretch was provided to the steering forearm by a custom-designed wearable skin-stretch device. We tested two hypotheses: i) an elderly individual’s motor control would benefit from receiving information about a desired trajectory from multiple sensory feedback sources, and ii) the benefit does not depend on task difficulty. Various metrics related to skills and safety were used to evaluate the control performance. Repeated measure ANOVA was performed for those metrics with two factors: task scenario and the type of the augmented sensory feedback. The results revealed that elderly subjects’ control performance significantly improved when the combined feedback of both haptic force and skin-stertch feedback was applied. The proposed approach suggest the feasibility to improve people’s task performance by the synergistic effects of multiple augmented sensory feedback modalities.